Papers published in Zootaxa concerning Nematoda from 2001 to 2020 - Hodda, Mike (Zootaxa, 2021)
In the first twenty years of the publication of Zootaxa, nearly 500 papers on nematodes have been published, ranging from complete classifications of the entire phylum to single species descriptions, revisions, catalogues and faunal checklists. In terms of species descriptions, this has represented a substantial and increasing proportion of all descriptions of new nematode species. A total of 488 authors have published, with over 20 authors contributing at a rate of more than one paper every two years.